Application of the Solvent Dimethyl Sulfoxide/Tetrabutyl‐Ammonium Acetate as Reaction Medium for Mix‐Acylation of Pulp. Issue 4 (4th September 2016) - Yu, Yongqi; Jiang, Zeming; Miao, Jiaojiao; Liu, Yang; Zhang, Liping
Abstract: An important cellulose mixed ester, cellulose acetate butyrate (CAB), was successfully prepared in tetrabutylammonium acetate (TBAA)/dimethyl sulfoxide (DMSO) system. The structure of the cellulose derivative was characterized with a Fourier Transform IR spectrometer and analyzed using 13 C cross‐polarization magic angle spinning nuclear magnetic resonance. The degree of substitution (DS) of the samples prepared was calculated according to 1 H‐NMR analysis. And the solubility of CAB was investigated in a wide range of traditional organic solvents such as 2‐methyl‐ethyl ketone, dichloromethane and ethyl acetate. The thermal properties of the product were analyzed by TGA analysis. The surface morphology of the esters was characterized with a field emission‐scanning electron microscopy (FE‐SEM). The relationship among surface morphology, solubility, and DS of the cellulose mixed ester was discussed. Moreover, TBAA and DMSO were recovered by vacuum distillation, which was characterized by Fourier transform infrared spectroscopy.